Analysis of the Implementation of Marketing Aspects in Cak Narto's Javanese Fried Rice MSME in a Business Feasibility Study - Allifna An Nauroh; Abdur Rohman (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2025)
MSMEs make a significant contribution to the Indonesian economy, particularly in terms of job creation and income distribution. However, challenges in marketing often hinder business development. This study aims to explore marketing aspects in the business feasibility study of Cak Narto's Javanese Fried Rice MSME in Surabaya using a descriptive qualitative approach. The analysis focuses on the elements of the marketing mix, including product, price, place, and promotion. The research findings indicate that, in terms of product, the business has a high level of feasibility due to the consistency of taste and the diversity of menu options offered. From a pricing perspective, the uniform and affordable pricing policy is considered effective in attracting and retaining customers. The strategic and easily accessible location of the business also supports its sustainability from a place perspective. However, the promotion aspect still has limitations, where marketing strategies rely more on direct communication and word-of-mouth methods, while the use of social media is still minimal. Therefore, optimizing digital promotion strategies is recommended to expand market reach and enhance the business's competitiveness. This study provides insights into the importance of marketing aspects in determining the viability and sustainability of culinary SMEs, while highlighting the need for innovation in marketing strategies to support more optimal business growth.